2019
DOI: 10.1093/geront/gnz111
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Experiences of People Over Age 50: Factor Structure and Validity of a Scale

Abstract: Background and Objectives Various aspects of the neighborhood environment have been shown to correlate with older adults’ health. Socio-ecological models of health posit that interventions in the living environment can influence population health. Yet, there are no scales to comprehensively measure older people’s experiences of their neighborhoods especially in dense urban contexts. This study analyzes the psychometric properties and factor structure of a holistic measure of Older People’s Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…The findings suggest that some of these factors are associated with both age and self-reported health condition. Such results correspond to some recent local studies which observed the connection between environmental conditions, going out and outdoor behaviour, and physical, psychological and social well-being of elderly residents (e.g., [ 115 , 116 , 117 , 118 , 119 ]). For instance, in their qualitative study, Bhuyan and Yuen [ 120 ] concluded that older adults tend to associate safety and pedestrian-friendly features with physical health, public amenities with social well-being, and aesthetic appeal and wayfinding with mental health.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings suggest that some of these factors are associated with both age and self-reported health condition. Such results correspond to some recent local studies which observed the connection between environmental conditions, going out and outdoor behaviour, and physical, psychological and social well-being of elderly residents (e.g., [ 115 , 116 , 117 , 118 , 119 ]). For instance, in their qualitative study, Bhuyan and Yuen [ 120 ] concluded that older adults tend to associate safety and pedestrian-friendly features with physical health, public amenities with social well-being, and aesthetic appeal and wayfinding with mental health.…”
Section: Discussionsupporting
confidence: 91%
“…Cao and colleagues [ 114 ], for instance, included an aesthetics category (nature, buildings, noise and cleanliness) to understand the out-of-home behaviour of older Singaporeans. In their study, Gan, Fung and Cho [ 115 ] proposed a holistic assessment of ‘Older People’s Neighborhood Experience’, which captured some elements of environmental pleasantness and outdoor aesthetics, such as appreciation of greenery, unique neighbourood features and different ambience qualities. Similarly, Hou and colleagues [ 116 ] considered both objective and subjective (perceived) measures of built environments in reference to older adults’ travel/walking behaviour, whereby perceived measures included those on aesthetics, cleanliness and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Future research may seek to understand plausible mechanisms by examining qualitative data of participants’ lived experiences and comparing across profiles. Community-level structural variables (e.g., neighborhood socioeconomic status) may alter individual experiences of the COVID-19 syndemic pandemic [ 20 , 47 , 48 , 49 ]. Qualitative methods are appropriate to “understand social processes or social structures … the settings, groups or individuals … which cannot be pre-selected” otherwise [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is not the first study that provides an instrument to measure people's neighborhood experiences (Buckner, 1988;Gan et al, 2020;Nasar & Julian, 1995;Peterson et al, 2008), digital media use in neighborhood contexts (Capece & Costa, 2013;Kavanaugh et al, 2005;Kim et al, 2019), nor is it the first to provide an instrument to measure social media use in a social capital framework (Appel et al, 2014;Ellison et al, 2007;Vitak, 2014;Williams, 2006). However, the ONNUS is the first instrument to measure social media use with respect to social relationship development and capitalization in a neighborhood context, thereby extending beyond ego-centered personal social networks.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, ONNUS is an instrument to measure a specific component of contemporary neighborhood life, making it complementary to other scales oriented towards neighborhood life (e.g. OpenX; Gan et al, 2020) for which online neighborhood life is a blind spot. As ONNs allow users to reach out to neighbors and networks of neighbors beyond their personal local social networks (De Meulenaere, Baccarne, et al, 2020), future studies could further investigate this intersection of in-person and online neighborhood relations and how these relations develop and are acted upon.…”
Section: Discussionmentioning
confidence: 99%